Komunikasi Interpersonal Kepala Sekolah dalam Penguatan Budaya Musyawarah di SD Negeri 2 Jatigunung - Sugiantoro, Erfan; Sulton, Sulton (Universitas Muhammadiyah Ponorogo, 2026)
As a means of shaping civic character, civics education does not merely focus on normative understanding of citizens’ rights and obligations, but also develops democratic values, moral awareness, and participation through everyday practices in school life. One fundamental value in civics education is deliberation (musyawarah), which is reflected in communication patterns, decision-making processes, and relationships among members of the school community. Schools function as social institutions with a strategic role in fostering a culture of deliberation through leadership and communication practices exercised by the principal. This study aims to analyze the principal’s interpersonal communication in strengthening the culture of deliberation at SDN 2 Jatigunung. The research employed a qualitative approach using a case study design. Data were collected through observations of school activities, in-depth interviews with the principal and teachers, and documentation of school policies and programs. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that dialogical, open, and empathetic interpersonal communication practiced by the principal encourages teacher participation and strengthens deliberative practices in school decision-making processes. The deliberative culture that develops contributes to the creation of a democratic and harmonious working climate and serves as a form of civics education practice that instills democratic values, responsibility, and togetherness in school life.